A flexible tissue–carbon nanocoil–carbon nanotube-based humidity sensor with high performance and durability. Issue 18 (26th April 2022) - Li, Chengwei; Zhang, Yifeng; Yang, Shuaitao; Zhao, Huitong; Guo, Yuan; Cong, Tianze; Huang, Hui; Fan, Zeng; Liang, Hongwei; Pan, Lujun
Abstract : A flexible humidity sensor based on a tissue–carbon nanocoil–carbon nanotube composite has been investigated. The sensor combines wide range, high sensitivity, fast response, high resolution, robust durability and wide application potential. Abstract : A flexible humidity sensor based on a tissue–carbon nanocoil (CNC)–carbon nanotube (CNT) composite has been investigated. Taking advantage of the excellent water absorption of tissue and the electrical sensitivity of CNCs/CNTs to humidity, this humidity sensor obtains outstanding humidity sensing performance, including a wide sensing range of 10–90% RH, a maximum response value of 492% (Δ R / R 0 ) at 90% RH, a maximum sensitivity of 6.16%/% RH, a good long-time stability of more than 7 days, a high humidity resolution accuracy of less than 1% RH and a fast response time of 275 ms. Furthermore, the sensor also exhibits robust bending (with a curvature of 0.322 cm −1 ) and folding (up to 500 times) durability, and after being made into a complex "thousand paper crane" shape it still provides stable humidity sensing performance. As a proof of concept, this humidity sensor demonstrates excellent responsivity to human breath monitoring, non-contact fingertip humidity detection, water boiling detection and air humidity monitoring, indicating great potential in the fields of wearable devices, weather forecasting systems and other intelligent humidity monitoring devices.